Online Teaching Amid the Covid-19 Pandemic: How Self-Efficacious Pre-service EFL Teachers Are? - Mercya Christ Sita Dewi; Kenti Sugiyati; Rachmah Yunita (Pascasarjana Universitas Negeri Makassar, 2022)
The sudden transition from an in-person class to online education due to the Covid-19 pandemic is not a new thing. Subsequently, it encourages educators to keep accommodating an effective learning environment. Studies agree that having a high level of self-efficacy in online teaching stands among the fields that educators need to have since it influences their behavior and motivation. Concerning this fact, the study intends to explore the self-efficacy of 53 pre-service EFL teachers who have already accomplished their online teaching practice. By distributing a self-administrated questionnaire, data revealed that pre-service teachers had a high level of self-efficacy on teaching online. The highest self-efficacy level was related to technology integration (m=4.75), followed by communicative language teaching (CLT) (m= 4.39), pedagogy (m=4.35), and the last; self-management (m=4.26). The findings also addressed that they had high self-efficacy to employ various online platforms to support and motivate students in online learning. Contrastingly, they had the lowest self-efficacy for managing their workload when teaching online. Come to an end, the study offers implications for education and teachers training programs to prepare their graduates to be accustomed to teaching online, considering the latest education need due to the Covid-19 pandemic.